Intimate partner violence and associated factors among married adolescent girls and young women in the pastoralist community of South Ethiopia: is intimate partner violence associated with cultural phenomena? - Namer, Ergudo; Shimbre, Mulugeta Shegaze; Alagaw, Amsalu; Guyo, Tamirat Gezahegn (Frontiers in Public Health, 2024)
Background Violence against women is a major public health problem that affects the physical, sexual, mental, and social wellbeing of more than one-third of all women worldwide. Hence the purpose of this study was to determine the prevalence of physical and sexual intimate partner violence (IPV) and associated factors among married adolescent girls and young women (AGYW) belonging to the pastoralist community of Dassenech district, South Omo Zone, South Ethiopia. Methods A community-based cross-sectional survey was conducted among married AGYW in the Dassenech district from March 1, 2022, to April 1, 2022. A multi-stage sampling technique was adopted to select 545 participants. The data were collected using pre-tested and standardized WHO multi-country study tools. A binary logistic regression model was fitted to identify the independent predictors of physical and sexual intimate partner violence. The adjusted odds ratio (AOR) with a 95% confidence interval (CI) was used to measure the effect size, and finally, a p-value<0.05 was considered statistically significant. Results The prevalence of physical IPV among AGYW belonging to the pastoralist community of Dassenech district was 44.1% (95% confidence interval (CI): 40%, 48%) and that of sexual IPV was 39.3% (95% CI: 35%, 43%). The husband only deciding for the household (AOR = 11.36; 95% CI: 6.97, 18.53), the father performing the Dimi cultural ceremony (AOR = 3.70; 95% CI: 2.22, 6.14), and frequent quarrels (AOR = 2.06; 95% CI: 1.07, 3.99) are significantly associated with physical IPV. Both partners drinking alcohol (AOR = 3.47; 95% CI: 1.94, 6.20), the husband only deciding for the household (AOR = 11.23; 95% CI: 6.91, 18.27), and frequent quarrels (AOR = 2.29; 95% CI: 1.15, 4.56) were factors significantly associated with sexual IPV. Conclusion Physical and sexual intimate partner violence is a significant public health problem in the study area. Therefore, interventional measures to change the attitude of cultural leaders, providing education to married men and women on risky sexual behavior, and empowering women need to be prioritized to prevent the occurrence of this problem.